Implementation of Zero Etanol in the Analysis of Lambucid Tablet Sampling at PT. Kalbe Farma Tbk - Nisa Nurhidayanti; Deni Rusli (Universitas Diponegoro, 2021)
PT. Kalbe Farma Tbk Bekasi is one of the pharmaceutical industries in Indonesia which has an essential role in the world of health because it produces several different preparations of drugs, one of which is lambucid tablets as medicine for heartburn. The ethanol waste produced in the production of lambucid tablets is toxic and can pollute the environment if it is not managed correctly. In testing the levels of the active substance in the Lambucid tablet product, it is known that the analysis process produces quite a lot of ethanol waste. This study aims to implement a method of developing the lambucid tablet production analysis test without making ethanol waste. The development method for removing ethanol in the analysis of lambucid tablet samples was carried out by replacing the titration method, which originally required quite a lot of ethanol to become an analytical method based on MA Tentative Promag Fruity Strawbery Tablet with number: MP-I 664253 A, this method has been tested by the team. RnD Andev PT.Kalbe Farma so that the data obtained are valid data with the advantage of not producing ethanol waste in each analysis. Through this method, the company can save Rp. 46.800.000 per year for the purchase of pure ethanol.